A kids book about : pride - Clawson, Kendall (Portland, OR : A Kids Book About, Inc, 2022)
In June, we celebrate Pride, but what does that mean? Everyone wants to be accepted just as they are, and Pride is all about honoring and encouraging people to be their most authentic selves! To help kids understand the enduring bravery of LGBTQIA+ people, this book includes the story of a moment in history which sparked the fight for freedom and acceptance for this community and beyond--something worth celebrating every day.
K-3
Keywords: Gender identity -- Juvenile literature; Sexual minorities. -- Juvenile literature; Transgender people -- Juvenile literature; Self-esteem -- Juvenile literature; Gender identity; Sexual orientation; Sexual minorities; LGBTQ+ nonfiction picture books